Esophageal varices predictive score in liver cirrhosis - Dala G Ashraf; Ibrahim El-Sayed (SpringerOpen, 2018)
Background Endoscopic surveillance of esophageal varices (EV) in patients with cirrhosis is expensive and uncomfortable for many patients. Therefore, there is a particular need for noninvasive predictors for EV. Objective The aim of the present study was to evaluate the accuracy of ultrasound and blood indices as noninvasive EV predictors among patients with cirrhosis. Patients and methods A total of 500 patients with cirrhosis were enrolled in this study and were divided according to their endoscopic findings into nonvariceal group (90 patients) and variceal group (410 patients). All patients underwent serum albumin, prothrombin time, aspartate aminotransferase, alanine aminotransferase, serum bilirubin, platelet count, hemoglobin level, abdominal ultrasonography (portal vein diameter and splenic size), and Child-Pugh score assessments. Results By evaluation of studied parameters, as predictors for EV, the splenic size was significant at cut-off greater than 13 cm. Platelet count was significant at a cut-off less than 12 3000/ml. Portal vein diameter was significant at a cut-off greater than 12 mm. Serum albumin was significant at a cut-off less than 3.2 g/dl. Prothrombin time was significant at a cut-off greater than 13.29 s. Child-Pugh score was significant with advanced scores. By multivariate regression analysis of the significant parameters, we reported that splenic size was the most significant parameter followed by platelet count followed by Child-Pugh score. EV prediction score can predict EV with sensitivity of 79.3, specificity of 83.3, and accuracy of 87.6%. Conclusion EV prediction score is a noninvasive parameter that can predict the presence of EV in patients with cirrhosis. Hence, its application may decrease the burden of endoscopy and provide a tool for selecting patients for whom endoscopy may be more beneficial.